Sendmail 8.13 companion - Costales, Bryan (O'Reilly, 2004)
"Bryan and Marcia have not only provided tips and tricks for detecting and blocking spam and email fraud but have also written the first of its kind Milter reference guide. This book will help you start writing your own special-purpose mail filters quickly and easily. Milters are among the most powerful antispamming tools available. Until now, there has been no clear and helpful resource for you to learn how to set up and use Milters. sendmail Milters: A Guide for Fighting Spam is the first in-depth guide to writing powerful Milters to block even the most clever spammers."
Includes index
Keywords: Sendmail; Electronic mail systems; Electronic Mail; Courrier électronique; electronic mail; Sendmail; Programm; Business & Economics; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Transportation Economics; Business & Management